An execration formula from Lugo (Lucus Augusti) - Simón, Francisco Marco (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
Excavations in the Plaza do Ferrol in Lugo (Galicia, Spain) during 1986 brought to light a necropolis with cistae datable from the middle of the 1st. century to the end of the 3rd. On one of the funeral urns (with a typology pointing to the first half of the 3rd. century) a graffito was written with a formula execrationis invoking “two genii” or, more probably, Duagena to punish the possible looters. This theonym, a hápax, seems to belong to a Celtic chtonic goddess whose personality (“Born Dark”, or “Born from Darkness”) finds parallels in other magical texts (e.g. antumnos in Larzac).